2012
DOI: 10.5301/jva.5000036
|View full text |Cite
|
Sign up to set email alerts
|

Totally Implantable Central Venous Access Ports in Patients with Cystic Fibrosis: A Multicenter Prospective Cohort Study

Abstract: Our data suggest that TIVADs represent a safe and effective device for the intermittent IV administration of drugs in people with CF. However, people with CFRD have a higher risk of developing TIVAD-related infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…In our cohort, aRBCX recipients were older and had more catheter complications, potentially reflecting this higher thrombosis risk in older patients. The catheter complication rates in our study and prior SCD studies are similar to those reported in children and adults with cystic fibrosis, ranging from 0.28 to 0.96/1,000 catheter days …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our cohort, aRBCX recipients were older and had more catheter complications, potentially reflecting this higher thrombosis risk in older patients. The catheter complication rates in our study and prior SCD studies are similar to those reported in children and adults with cystic fibrosis, ranging from 0.28 to 0.96/1,000 catheter days …”
Section: Discussionsupporting
confidence: 87%
“…The catheter complication rates in our study and prior SCD studies are similar to those reported in children and adults with cystic fibrosis, ranging from 0.28 to 0.96/1,000 catheter days. [18][19][20] There have been no prospective studies comparing effectiveness of recipients were more likely to meet their Hb S goal before at least twothirds of transfusions. 21 Duclos et al compared five children receiving aRBCX with five receiving MET, concluding that for all transfusion events, Hb S control was similar, but for transfusion events less than 40 days apart, aRBCX resulted in lower pretransfusion Hb S. 22 Finally, Fasano et al 6 and Koehl et al 23 reported similar pretransfusion Hb S F I G U R E 3 Achievement of pretransfusion hemoglobin (Hb) S goals (A) No difference in fraction of visits achieving Hb S goal between erythrocytapheresis (aRBCX) recipients compared with nonrecipients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher rate in the latter study was likely related to its prospective, single center design. The mean complication-free survival time for TIVADs of 1009 days (median 1266 days) was comparable to that reported by others [8][9][10][11]16]. Our overall TIVAD complication rate is considerably less than reported by Italian centers [16] and an Australian center [11], and is closer to the rate of a center in the United Kingdom [17].…”
Section: Line Complicationssupporting
confidence: 84%
“…Device exposure to continuous turbulent flow may be among the predisposing factors for IE. In addition to intermittent bacteremia due to CF, CFRDM may have contributed to the pathophysiology of endocarditis (9). …”
Section: Discussionmentioning
confidence: 99%